2019
DOI: 10.1152/ajpgi.00404.2018
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal serine protease inhibition increases FGF21 and improves metabolism in obese mice

Abstract: Trypsin is the major serine protease responsible for intestinal protein digestion. An inhibitor, camostat (CS), reduced weight gain, hyperglycemia, and dyslipidemia in obese rats; however, the mechanisms for these are largely unknown. We reasoned that CS creates an apparent dietary protein restriction, which is known to increase hepatic fibroblast growth factor 21 (FGF21). Therefore, metabolic responses to CS and a gut-restricted CS metabolite, FOY-251, were measured in mice. Food intake, body weight, blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Recently, in vivo enteropeptidase inhibition by SCO‐792 was demonstrated to be highly effective in improving the disease status of diabetes and obesity in mouse models . In addition, inhibition of intestinal trypsin, which is a downstream molecule of enteropeptidase, was shown to decrease body weight and improve metabolism in leptin‐deficient and DIO mice . Taken these together, protein digestion inside the gut likely to have a significant role in regulating body weight and metabolism and inhibiting this step may be a rational strategy to improve obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in vivo enteropeptidase inhibition by SCO‐792 was demonstrated to be highly effective in improving the disease status of diabetes and obesity in mouse models . In addition, inhibition of intestinal trypsin, which is a downstream molecule of enteropeptidase, was shown to decrease body weight and improve metabolism in leptin‐deficient and DIO mice . Taken these together, protein digestion inside the gut likely to have a significant role in regulating body weight and metabolism and inhibiting this step may be a rational strategy to improve obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that camostat mesylate treatment reduced the incidence of new-onset diabetes mellitus in patients with chronic pancreatitis 172 . This drug improved glycaemia and insulin resistance and decreased lipid accumulation in animal models 173 , 174 . The antimalaria drugs chloroquine and hydroxychloroquine have been used to treat SARS-CoV-2 infection despite their potential adverse effects 175 , 176 .…”
Section: Covid-19 Treatments and Metabolismmentioning
confidence: 99%
“…90 Since then, no human studies have been performed to further elucidate the role of trypsin secretion in obesity. 91 The latter hampers the optimization of efforts that use trypsin inhibition to reduce body weight.…”
Section: Pancreatic Trypsinmentioning
confidence: 99%